Association Between Thyroid Function Parameters and Plasma Branched-Chain Amino and Keto Acids in Patients With Euthyroid Type 2 Diabetes Mellitus - Xinghua Cai; Yuanying Xu; Jie Gao; Huihui Zhang; Jun Lu; Tao Lei (Journal of Diabetes Research)
Conclusions: Thyroid function parameters positively correlated with plasma BCAAs but negatively correlated with plasma BCKAs in patients with euthyroid T2DM. However, further prospective studies are needed to explore potential causal relationships and verify these findings.